Engineer/scientist careers: Patents, online profiles, and misclassification bias - Ge, Chunmian; Huang, Ke‐Wei; Png, Ivan P. L. (Strategic Management Journal, 2016)
Research summary : This article applies data from LinkedIn to advance strategy research into the effect of human capital on mobility of engineers and scientists. Through an inventor survey, we show that LinkedIn provides more accurate career histories than patents. Compared to LinkedIn , patent measures of mobility generate 12 percent false positives and 83 percent false negatives. Using LinkedIn , we review findings from previous research using patents to track the effect of human capital on mobility. One previous finding is robust: that mobility is higher in Silicon Valley than elsewhere. Other findings are possibly sensitive to the measure of mobility or sample selection. We interpret our results as the outcome of targeted retention of human capital. Data for this study may be accessed at FIVE, five.dartmouth.edu . Managerial summary : How does the mobility of engineers and scientists depend on their human capital? Previous research used patents to track inventor mobility and concluded that employers targeted inventors for recruitment by their human capital. Here, we introduce data from LinkedIn to review the previous research. Through an inventor survey, we show that LinkedIn provides more accurate career histories than patents. Compared to LinkedIn, patent measures of mobility generate 12 percent false positives and 82 percent false negatives. Among the previous findings, we show that one is robust: mobility is higher among inventors in Silicon Valley than elsewhere. Other findings are possibly sensitive to the measure of mobility or sample selection. Our results suggest that current employers target engineers and scientists for retention according to their human capital . Copyright © 2015 John Wiley & Sons, Ltd.